Characteristics, management, and outcomes of patients with hepatocellular carcinoma in Africa: a multicountry observational study from the Africa Liver Cancer Consortium. (February 2017) - Yang, Ju Dong; Mohamed, Essa A; Aziz, Ashraf O Abdel; Shousha, Hend I; Hashem, Mohamed B; Nabeel, Mohamed M; Abdelmaksoud, Ahmed H; Elbaz, Tamer M; Afihene, Mary Y; Duduyemi, Babatunde M; Ayawin, Joshua P; Gyedu, Adam; et al.
Summary: Background: Hepatocellular carcinoma is a leading cause of cancer-related death in Africa, but there is still no comprehensive description of the current status of its epidemiology in Africa. We therefore initiated an African hepatocellular carcinoma consortium aiming to describe the clinical presentation, management, and outcomes of patients with hepatocellular carcinoma in Africa. Methods: We did a multicentre, multicountry, retrospective observational cohort study, inviting investigators from the African Network for Gastrointestinal and Liver Diseases to participate in the consortium to develop hepatocellular carcinoma research databases and biospecimen repositories. Participating institutions were from Cameroon, Egypt, Ethiopia, Ghana, Ivory Coast, Nigeria, Sudan, Tanzania, and Uganda. Clinical information—demographic characteristics, cause of disease, liver-related blood tests, tumour characteristics, treatments, last follow-up date, and survival status—for patients diagnosed with hepatocellular carcinoma between Aug 1, 2006, and April 1, 2016, were extracted from medical records by participating investigators. Because patients from Egypt showed differences in characteristics compared with patients from the other countries, we divided patients into two groups for analysis; Egypt versus other African countries. We undertook a multifactorial analysis using the Cox proportional hazards model to identify factors affecting survival (assessed from the time of diagnosis to last known follow-up or death). Findings: We obtained information for 2566 patients at 21 tertiary referral centres (two in Egypt, nine in Nigeria, four in Ghana, and one each in the Ivory Coast, Cameroon, Sudan, Ethiopia, Tanzania, and Uganda). 1251 patients were from Egypt and 1315 were from the other African countries (491 from Ghana, 363 from Nigeria, 277 from Ivory Coast, 59 from Cameroon, 51 from Sudan, 33 from Ethiopia, 21 from Tanzania, and 20 from Uganda). The median age at which hepatocellular carcinoma was diagnosed significantly later in Egypt than the other African countries (58 years [IQR 53–63] vs 46 years [36–58]; p<0·0001). Hepatitis C virus was the leading cause of hepatocellular carcinoma in Egypt (1054 [84%] of 1251 patients), and hepatitis B virus was the leading cause in the other African countries (597 [55%] of 1082 patients). Substantially fewer patients received treatment specifically for hepatocellular carcinoma in the other African countries than in Egypt (43 [3%] of 1315 vs 956 [76%] of 1251; p<0·0001). Among patients with survival information (605 [48%] of 1251 in Egypt and 583 [44%] of 1315 in other African countries), median survival was shorter in the other African countries than in Egypt (2·5 months [95% CI 2·0–3·1] vs 10·9 months [9·6–12·0]; p<0·0001). Factors independently associated with poor survival were: being from an African countries other than Egypt (hazard ratio [HR] 1·59 [95% CI 1·13–2·20]; p=0·01), hepatic encephalopathy (2·81 [1·72–4·42]; p=0·0004), diameter of the largest tumour (1·07 per cm increase [1·04–1·11]; p<0·0001), log α-fetoprotein (1·10 per unit increase [1·02–1·20]; p=0·0188), Eastern Cooperative Oncology Group performance status 3–4 (2·92 [2·13–3·93]; p<0·0001) and no treatment (1·79 [1·44–2·22]; p<0·0001). Interpretation: Characteristics of hepatocellular carcinoma differ between Egypt and other African countries. The proportion of patients receiving specific treatment in other African countries was low and their outcomes were extremely poor. Urgent efforts are needed to develop health policy strategies to decrease the burden of hepatocellular carcinoma in Africa. Funding: None.